VOCATIONAL TRAINING ISCED 3C IN THE CONTEXT OF THE SCHOOL REFORM - ZATKALIK, Martin; HASKOVA, Alena (Trends in education, 2012)
In their paper the authors assess impact of the system of state and school education programmes, introduced within the school reform, on the quality of vocational training. For a deeper view of the discussed issues they use motor-car repair study branches as an example.
Keywords: state/school education programme; technical education proportion on professional training; professional training material and technical conditions; recommendation proposal.